2D Layered Graphene Oxide Films Integrated with Micro‐Ring Resonators for Enhanced Nonlinear Optics. Issue 16 (11th March 2020) - Wu, Jiayang; Yang, Yunyi; Qu, Yang; Jia, Linnan; Zhang, Yuning; Xu, Xingyuan; Chu, Sai T.; Little, Brent E.; Morandotti, Roberto; Jia, Baohua; Moss, David J.
Abstract: Layered 2D graphene oxide (GO) films are integrated with micro‐ring resonators (MRRs) to experimentally demonstrate enhanced nonlinear optics. Both uniformly coated (1−5 layers) and patterned (10−50 layers) GO films are integrated on complementary‐metal‐oxide‐semiconductor (CMOS)‐compatible doped silica MRRs using a large‐area, transfer‐free, layer‐by‐layer GO coating method with precise control of the film thickness. The patterned devices further employ photolithography and lift‐off processes to enable precise control of the film placement and coating length. Four‐wave‐mixing (FWM) measurements for different pump powers and resonant wavelengths show a significant improvement in efficiency of ≈7.6 dB for a uniformly coated device with 1 GO layer and ≈10.3 dB for a patterned device with 50 GO layers. The measurements agree well with theory, with the enhancement in FWM efficiency resulting from the high Kerr nonlinearity and low loss of the GO films combined with the strong light–matter interaction within the MRRs. The dependence of GO's third‐order nonlinearity on layer number and pump power is also extracted from the FWM measurements, revealing interesting physical insights about the evolution of the GO films from 2D monolayers to quasi bulk‐like behavior. These results confirm the high nonlinear optical performance of integrated photonic resonators incorporated with 2D layered GO films. Abstract : Layered 2D graphene oxide (GO) films are integrated with complementary‐metal‐oxide‐semiconductor (CMOS)‐compatible micro‐ring resonators to demonstrate enhanced nonlinear optics via four‐wave mixing (FWM). Up to 7.6 and 10.3 dB improvements of FWM conversion efficiency are achieved for the uniformly coated and patterned devices, respectively. The dependence of GO's third‐order nonlinearity on layer number and light power is also extracted and analyzed.